Holistic quantum design of thermoelectric niobium oxynitride. (June 2015) - Music, Denis; Bliem, Pascal; Hans, Marcus
Abstract: We have applied holistic quantum design to thermoelectric NbON (space group Pm -3 m ). Even though transport properties are central in designing efficient thermoelectrics, mechanical properties should also be considered to minimize their thermal fatigue during multiple heating/cooling cycles. Using density functional theory, elastic constants of NbON were predicted and validated by nanoindentation measurements on reactively sputtered thin films. Based on large bulk-to-shear modulus ratio and positive Cauchy pressure, ceramic NbON appears ductile. These unusual properties may be understood by analyzing the electronic structure. Nb–O bonding is of covalent–ionic nature with metallic contributions. Second neighbor O–N bonds exhibit covalent–ionic character. Upon shear loading, these O–N bonds break giving rise to easily shearable planes. Ductile NbON, together with large Seebeck coefficient and low thermal expansion, is promising for thermoelectric applications. Highlights: Cubic NbON is a promising thermoelectric phase. To explore its thermal fatigue, mechanical properties were explored. Ceramic NbON appears ductile due to presence of shearable planes. Low linear coefficient of thermal expansion is predicted. Based on these properties, low thermal fatigue is expected.